Different gene-specific mechanisms determine the 'revised-response' memory transcription patterns of a subset of A. thaliana dehydration stress responding genes. Issue 9 (17th April 2014) - Liu, Ning; Ding, Yong; Fromm, Michael; Avramova, Zoya
Abstract: Plants that have experienced several exposures to dehydration stress show increased resistance to future exposures by producing faster and/or stronger reactions, while many dehydration stress responding genes in Arabidopsis thaliana super-induce their transcription as a 'memory' from the previous encounter. A previously unknown, rather unusual, memory response pattern is displayed by a subset of the dehydration stress response genes. Despite robustly responding to a first stress, these genes return to their initial, pre-stressed, transcript levels during the watered recovery; surprisingly, they do not respond further to subsequent stresses of similar magnitude and duration. This transcriptional behavior defines the 'revised-response' memory genes. Here, we investigate the molecular mechanisms regulating this transcription memory behavior. Potential roles of abscisic acid (ABA), of transcription factors (TFs) from the ABA signaling pathways (ABF2/3/4 and MYC2), and of histone modifications (H3K4me3 and H3K27me3) as factors in the revised-response transcription memory patterns are elucidated. We identify the TF MYC2 as the critical component for the memory behavior of a specific subset of MYC2-dependent genes.